Simultaneous occurrence of autoimmune pancreatitis and pancreatic cancer in patients resected for focal pancreatic mass - Macinga, Peter (World J Gastroenterol, 2017)
AIM: To assess the occurrence of autoimmune pancreatitis (AIP) in pancreatic resections performed for focal pancreatic enlargement. METHODS: We performed a retrospective analysis of medical records of all patients who underwent pancreatic resection for a focal pancreatic enlargement at our tertiary center from January 2000 to July 2013. The indication for surgery was suspicion of a tumor based on clinical presentation, imaging findings and laboratory evaluations. The diagnosis of AIP was based on histology findings. An experienced pathologist specialized in pancreatic disease reviewed all the cases and confirmed the diagnosis in pancreatic resection specimens suggestive of AIP. The histological diagnosis of AIP was set according to the international consensus diagnostic criteria. RESULTS: Two hundred ninety-five pancreatic resections were performed in 201 men and 94 women. AIP was diagnosed in 15 patients (5.1%, 12 men and 3 women) based on histology of the resected specimen. Six of them had AIP type 1, nine were diagnosed with AIP type 2. Pancreatic adenocarcinoma (PC) was also present in six patients with AIP (40%), all six were men. Patients with AIP + PC were significantly older (60.5 vs 49 years of age, P = 0.045), more likely to have been recently diagnosed with diabetes (67% vs 11%, P = 0.09), and had experienced greater weight loss (15.5 kg vs 8.5 kg, P = 0.03) than AIP patients without PC. AIP was not diagnosed in any patients prior to surgery; however, the diagnostic algorithm was not fully completed in every case. CONCLUSION: The possible co-occurrence of PC and AIP suggests that preoperative diagnosis of AIP does not rule out simultaneous presence of PC.